Strong convergence to solutions of generalized mixed equilibrium problems with applications - Prasit Cholamjiak (2018)
We introduce a Halpern-type iteration for a generalized mixed equilibrium problem in uniformly smooth and uniformly convex Banach spaces. Strong convergence theorems are also established in this paper. As applications, we apply our main result to mixed equilibrium, generalized equilibrium, and mixed variational inequality problems in Banach spaces. Finally, examples and numerical results are also given. © 2012 Prasit Cholamjiak et al.